Human Piebaldism: Six Novel Mutations of the Proto-oncogene KIT - ELÇİOĞLU, HURİYE NURSEL (WILEY-BLACKWELL, 2002)
Human piebaldism is a rare autosomal dominant disorder that comprises congenital patchy depigmentation of the scalp, forehead, trunk and limbs. It is caused by mutations in the cell-surface receptor tyrosine kinase gene (KIT, also c-kit). We screened three families and three isolated cases of piebaldism from different countries for mutations in the KIT gene using automated sequencing methods. We report six novel KIT point mutations: three missense (C788R, W835R, P869S) at highly conserved amino acid sites; one nonsense (Q347X) that results in termination of translation of the KIT gene in exon 6; and two splice site nucleotide substitutions (IVS13+2T>G, IVS17-1G>A) that are predicted to impair normal splicing. These mutations were not detected in over 100 normal individuals and are likely to be the cause of piebaldism in our subjects. (C) 2002 Wiley-Liss, Inc.
Keywords: Piebaldism; proto-oncogene; KIT; mutation screen